THE INFLUENCE OF NON-STATE ACTORS ON GLOBAL POLICY-MAKING - Faiza Idrees (Journal of Religion and Society, 2024)
This article investigates a non-state actor’s growing participation in global policymaking, which is an attempt to challenge the unitary state perspective of international relations. The growing globalization of the world economy has led to the emergence and proliferation of non-state actors such as NGOs, multinational enterprises, and transnational advocacy networks which have been actively involved in the formulation of global policies especially in the areas of environmental governance and human rights. These actors are often more agile and responsive than formal government institutions, which enables them to make a difference in global policy. This analysis looks at how non-state actors influence policy processes, and more importantly, the factors that determine their success or failure in achieving desired objectives. Theoretical frameworks that include pluralism and network theory guide the author’s analysis of the relevant non-state actors, their interrelations, and their relations to state actors and participation in international policymaking in an attempt to understand the complete picture. The analysis underscores the ambiguity of non-state actors: who, on the one hand, advance positive agendas and encourage international cooperation, their impact on issues and problems differ greatly in magnitude on the other hand. This paper aims at understanding the role of non-state actors in global governance and international relations gives them a deep analysis of their activity in the modern world. Keywords: Non-State Actors, Global Policymaking, International Relations, Pluralism, Transnational Advocacy Networks, Environmental Governance, Global Governance